2021
DOI: 10.1007/s00246-021-02632-y
|View full text |Cite
|
Sign up to set email alerts
|

QRS Duration During Follow-Up of Tetralogy of Fallot: How Valuable is it? Analysis of ECG Changes in Relation to Pulmonary Valve Implantation

Abstract: Long-term results after tetralogy of Fallot (TOF) repair are determined by the extent of right ventricular remodeling to chronic pulmonary regurgitation entailing progressive RV dysfunction and a risk of developing ventricular arrhythmia. Pulmonary valve replacement (PVR) can alleviate this burden. As a predictor of ventricular arrhythmia, QRS duration remains a strong parameter in this decision. We performed a retrospective analysis of all PVR patients between 2005 and 2018, studying the time evolution of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Multiple studies have shown that QRS duration is closely related to RV dilatation (14). Guidelines from the European Society of Cardiology suggest that QRS duration >180mms be used as an indication of PVR (14,17). However, in our research cohort, there was no signi cant difference between groups in QRS duration, even in the RV moderate-severe dilatation group, the median QRS duration was still less than 180mms.…”
Section: Preoperative Clinical Featurescontrasting
confidence: 62%
See 1 more Smart Citation
“…Multiple studies have shown that QRS duration is closely related to RV dilatation (14). Guidelines from the European Society of Cardiology suggest that QRS duration >180mms be used as an indication of PVR (14,17). However, in our research cohort, there was no signi cant difference between groups in QRS duration, even in the RV moderate-severe dilatation group, the median QRS duration was still less than 180mms.…”
Section: Preoperative Clinical Featurescontrasting
confidence: 62%
“…Cardiac electrophysiology is an important evaluation method for patients with rTOF, and the presence of persistent arrhythmias before surgery often indicates a poor prognosis (14-16). Multiple studies have shown that QRS duration is closely related to RV dilatation (14). Guidelines from the European Society of Cardiology suggest that QRS duration >180mms be used as an indication of PVR (14,17).…”
Section: Preoperative Clinical Featuresmentioning
confidence: 99%
“…The right ventricular end-diastolic volume index was greater in the SPVR group (184 mL/m 2 [163-230]) than in the TPVR group (165 mL/m 2 [136-190]; P ¼ .001). The maximum PV landing zone diameter measured by balloon sizing (Figure 1) was 24 mm (20-26.5) in the TPVR group and 30 mm (26)(27)(28)(29)(30)(31)(32)(33) in the SPVR group (P < .001) (Table 2). Excluding patients with RVOT conduit, the median size of the PV landing zone in patients with RVOT was 26 mm (24-28) in the 43 patients who underwent TPVR and 31 mm (28)(29)(30)(31)(32)(33)(34) in the 101 patients who underwent SPVR (P < 0.001) (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…However, this was not significant in the immediate postoperative period. QRS duration and cardiac MRI findings are correlated with postoperative patients with TOF, [25][26][27] and these arrhythmias can predict survival. [2][3][4]28 Therefore, we assessed the QRS duration as a surrogate variable for RV dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital diseases may eventually manifest during adulthood in response to specific stresses, remaining undiscovered until a dramatic or fatal episode occurs, even in agonistic athletes routinely submitted to ECG to practice [102][103][104][105][106][107][108][109][110][111]. Acquired rhythm pathologies might be induced by several causes, among which drug cardiotoxicity, cardiomyopathies, myocarditis or systemic infections, valve diseases, and interventional/surgical maldeployment of cardiac valve replacements [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128].…”
Section: Heart Rhythm Diseases: Clinical Signs Underlying Causes and Modeling Approachesmentioning
confidence: 99%